The Integration of Electricity Markets in Central Europe in the Frame of Energy Union - Farkač, Pavel (2016)
This paper examines the possibilities for further integration of day-ahead electricity market in Central Europe. The contemporary situation is locked due to the existence of the German-Austria bidding zone. However, compliance of this bidding zone with European legislative is questionable. Therefore, the author makes a thorough legal analysis to assess the compatibility of both analysed projects for market coupling with the recent legal development in the European Union. Further, the examined projects are technically deconstructed in order to evaluate their conformity or differences between each other as well as in relation towards the EU Target Model. It is assessed, that both projects are relatively well technically compatible, however, their merger is not possible until the definite and binding decision on the issue of German-Austrian bidding zone will be found.